2020
DOI: 10.1177/0954008320983412
|View full text |Cite
|
Sign up to set email alerts
|

Reactive molecular dynamics simulation on the pyrolysis characteristics of epoxy resin under the effect of partial discharge active products

Abstract: Aromatic amine cured Bisphenol F epoxy resin is used as a pivotal solid insulation material in electrical equipment at low temperature and extreme environment. Partial discharge (PD) can lead to an increase in local temperature, which leads to pyrolysis, and the existence of PD active products will aggravate the pyrolysis process of insulating materials. In order to investigate the effect of PD active products on the pyrolysis characteristics of aromatic amine cured epoxy resin, the pyrolysis process of epoxy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The distorted electric field that initiates electrical partial discharge in insulation materials used for high-voltage power system will reach hundreds of kV/mm, and the electrical partial discharge can promptly increase the local temperature to thousands of Kelvin. In addition, it has been demonstrated by reactive MD simulations that a higher specified value of simulation temperature and heating rate result in a higher speed and a lower initial temperature of polymer thermal decomposition, respectively, while neither of them evidently account for product species and decomposition reaction path [ 20 , 32 , 33 ]. To elucidate the chemical corrosion under extremely high electric field of partial discharges, the active molecules generally produced by partial discharges are modeled and added into the crosslinked EP models to perform NVT MD simulations for 50 ps under 0.001~0.01 V/Å electrostatic fields, in which the sharp temperature increasing (heating) rate is adopted to simulate thermal effect of partial discharges.…”
Section: Reactive Molecular Dynamics Simulationmentioning
confidence: 99%
“…The distorted electric field that initiates electrical partial discharge in insulation materials used for high-voltage power system will reach hundreds of kV/mm, and the electrical partial discharge can promptly increase the local temperature to thousands of Kelvin. In addition, it has been demonstrated by reactive MD simulations that a higher specified value of simulation temperature and heating rate result in a higher speed and a lower initial temperature of polymer thermal decomposition, respectively, while neither of them evidently account for product species and decomposition reaction path [ 20 , 32 , 33 ]. To elucidate the chemical corrosion under extremely high electric field of partial discharges, the active molecules generally produced by partial discharges are modeled and added into the crosslinked EP models to perform NVT MD simulations for 50 ps under 0.001~0.01 V/Å electrostatic fields, in which the sharp temperature increasing (heating) rate is adopted to simulate thermal effect of partial discharges.…”
Section: Reactive Molecular Dynamics Simulationmentioning
confidence: 99%
“…Aliphatic structures in cycloaliphatic epoxy tend to be more resistant to oxidation and UV degradation than aromatic structures because they lack excitable π electrons (red in Figure 3c). Moreover, the saturated nature of this structure offers good chemical stability [99][100][101][102]. Extensive studies in the literature reported modifying monomers and additives to meet the requirements of PSC encapsulation, including water-vapor barrier properties, sensitivity to UV irradiation, low susceptibility to cracking, and excellent weather resistance.…”
Section: The Design Of Uv-curable Resin For Psc Encapsulationmentioning
confidence: 99%
“…Before the establishment of the cross-linked epoxy resin model, the periodicity of the model in the Z-axis direction is blocked by adding a vacuum layer of 15 Å , in which the argon molecular layer is filled. The cross-linking process of the model in the Z-direction is isolated to establish the periodic interface model on the XOY plane and then cross-link the amorphous model [24]. After the cross-linking procedure is completed, the argon molecular layer on the surface is deleted, and a surface model of cross-linked epoxy resin with 95% degree of cross-linking is obtained.…”
Section: Model Buildingmentioning
confidence: 99%
“…After the cross-linking procedure is completed, the argon molecular layer on the surface is deleted, and a surface model of cross-linked epoxy resin with 95% degree of cross-linking is obtained. The obtained model is imported into AMS software and a density of 1.19 g/cm 3 model is obtained by 100 ps relaxation at 298 K and 0.1013 MPa using NPT system [24]. The addition of a vacuum layer in the Z-axis of the cell provides space for the motion of energetic particles, and the final cell volume is 30.195793 Å × 30.195793 Å × 100.00 Å .…”
Section: Model Buildingmentioning
confidence: 99%